PENGARUH KUALITAS LAYANAN DAN BIAYA PENDIDIKAN TERHADAP KEPUASAN ORANG TUA - Zelin Ferdias Capriati; Yossy Wahyu Indrawan; Kiki Dwi Wijayanti (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to examine the effect of service quality and education costs on parents satisfaction at kindergarten. The research used a quantitative approach with a survey method involving 120 parents of students as respondents. Data were collected using Likert-scale questionnaires and analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination with SPSS. The results show that service quality has a positive and significant effect on parents satisfaction. Education costs also have a positive and significant effect on parents satisfaction. Simultaneously, service quality and education costs significantly affect parents satisfaction with an R-square value of 0.642, indicating that 64.2% of parents satisfaction can be explained by the two independent variables. These findings imply that schools need to improve service responsiveness, teacher-parent communication, facility quality, and transparent education cost management to increase parents trust and satisfaction.